Mechanical Properties of Cement-Stabilized Sandy Soils Modified with Consoil - Ahmed, Mustafa I.; Abed, Alaa H. (Salehan Institute of Higher Education, 2025)
This study investigates the mechanical enhancement of sandy soils through cement stabilization modified with Consoil, targeting improved pavement substructure performance. Unconfined compressive strength (UCS) tests were conducted on samples with varying cement contents (3%, 6%, 9%), Consoil dosages (0%, 5%, 10%, 15%, 20% by cement weight), and curing periods (3, 7, 28, 90 days). Field Emission Scanning Electron Microscopy and X-Ray Diffraction analyses complemented mechanical testing to understand strengthening mechanisms. Results demonstrated that 15% Consoil consistently optimized strength development across all cement contents, with 9% cement and 15% Consoil achieving peak 90-day UCS of 17.74 MPa, representing a 67% increase over control samples. Microstructural analysis revealed progressive matrix refinement with increasing Consoil content, while XRD indicated enhanced pozzolanic activity through calcium hydroxide consumption. The study introduces Consoil as an effective stabilization additive, establishing optimal dosage rates and demonstrating significant strength improvements through synergistic cement-Consoil interactions. The findings provide new insights into strength enhancement mechanisms in Consoil-modified cement-stabilized soils, offering practical guidelines for designing high-performance pavement substructures. The research contributes to sustainable construction practices by optimizing cement usage through Consoil incorporation. Doi: 10.28991/CEJ-2025-011-01-011 Full Text: PDF